Nephrotoxicity of iodinated contrast media: From pathophysiology to prevention strategies - Faucon, Anne-Laure; Bobrie, Guillaume; Clément, Olivier (European journal of radiology, 2019)
•ICM-induced AKI is the third most common cause of acute renal failure in hospitalized patients.•“ICM-induced AKI” is defined as AKI caused by the ICM per se. “Post contrast-induced AKI” should be used for AKI following ICM injection, without evidence of direct renal toxicity.•ICM-induced AKI is the result of a direct toxicity of ICM for epithelial and endothelial cells, the impairment of renal hemodynamics, the rheological properties and administration modalities.•The most significant risk factor for developing AKI is pre-existing CKD.•The 2018-ESUR guidelines recommend using the KDIGO definition of AKI: an increase in serum creatinine ≥26.5 μmol/L (0.3 mg/dl), or ≥1.5-1.9 times baseline, within 48–72 h following ICM administration.•Hydration is the cornerstone of preventive treatment. Iodinated contrast media (ICM) induced acute kidney injury (AKI) accounts for 11% of cases of AKI and is its third most common cause in hospitalized patients. However, the pathophysiological mechanisms are not yet completely understood. The nephrotoxicity of ICM is partly the consequence of a direct cytotoxic effect on renal tubular epithelial and endothelial cells. It is also the consequence of impaired intrarenal hemodynamics, these two mechanisms being closely linked. The rheological properties of ICM, the volume infused, and the route of administration increase the intrinsic toxicity generated by the contrast media used. Furthermore, various clinical situations increase the risk of developing AKI. There is no specific treatment. Hydration is the cornerstone of prevention. Preventive measures have reduced the incidence of AKI over the last ten years. After an overview of the pathophysiology of the renal toxicity of ICM, we review risk factors and scores, diagnosis, and means of prevention in the light of the 2018 European Society of Urogenital Radiology and the 2018 American College of Radiology guidelines and recent studies on the subject. In addition, a side-by-side comparison of the updated and less conservative guidelines from the Radiology community and the more cautionary attitude from the Nephrology community are also presented.